Comprehensive study of high pressure annealing on the ferroelectric properties of Hf0.5Zr0.5O2 thin films. (1st October 2019) - Oh, Changyong; Tewari, Amit; Kim, Kyungkwan; Kumar, Ulayil Sajesh; Shin, Changhwan; Ahn, Minho; Jeon, Sanghun
Abstract: Thin films of ferroelectric materials are potential candidates to be implemented in the unfolding of a new paradigm in high-density memory devices. As the thickness of these films reaches the sub-10 nm level, the interface properties between the electrode and ferroelectric material undergo significant changes that play a crucial role in governing the ferroelectric behavior. The present state-of-the-art approach presents a detailed investigation of different high pressure annealing (HPA) conditions through simulation studies. The simulation studies were performed using Landau–Khalatnikov equations, with Landau's parameters calculated using the least regression method as described in the Method S1. The extracted coefficients were used to determine various relationships (free energy, ferroelectric potential and negative capacitance) with which to observe the impact of HPA on the negative capacitance (NC) effect on account of the majority ferroelectric phase. To verify the simulation results, pulse transient switching measurements were conducted using Pt/Ti/TiN/Hf0.5 Zr0.5 O2 /TiN-based metal-ferroelectric-metal (MFM) devices to study the coercive field, interfacial capacitance and load resistance behavior. The results suggest that the non-ferroelectric portion (t-phase) coexists with the ferroelectric (o-phase) within the thin layer of the MFM capacitor adjacent to TiN electrode, which undergoes a phase transformation from the t-phase to the o-phase when exposed to different HPA conditions as well as electric field cycling during PS measurements. The simulation and experimental results confirm that the 550 °C at 50 atm N2 environment provides the best possibility of achieving the highest ferroelectric characteristics with the lowest proportion of the non-ferroelectric phase and thus the maximum NC effect as well.